Tablighi Jama’ah and Politics - Bukhori Bukhori; Dzar Al Giftar (Politicon : Jurnal Ilmu Politik, 2023)
This research addresses the prevalent community rumors regarding the Tablighi Jama'ah's aversion to political discourse. The veracity of this claim is confirmed through an examination of the Jama'ah's foundational teachings, notably the "20 Principles of Da'wah," where it explicitly proscribes discussions on both domestic and foreign politics. The inquiry into how a community dedicated to molding Muslim individuals and societies can effect change while restricting political dialogue serves as the central query. Employing a descriptive analytical method with a qualitative approach, the study employs three distinct data collection techniques—Observation, Interview, and Literature Study. Qualitative data analysis unfolds through successive stages of data reduction, data display, and conclusion/verification. From field findings and subsequent discussions, two key conclusions emerge: Firstly, the Tabligh Jama'ah successfully molds Muslim individuals and communities in Temboro Village, Karas District, Magetan Regency, by adhering to core teachings under the guidance of experienced masyayikh. Secondly, the Jama'ah is renowned as non-political; a label that doesn't signify complete disengagement from politics, but rather refraining from overt political discussions. The focus instead lies in eschewing practical politics. In essence, the Tabligh Jama'ah represents a practical non-political entity. As a recommendation, this study underscores the necessity for further research into the Muslim community of Temboro Village, employing a multidisciplinary approach. Given its empirical significance, the community's dynamics have the potential to serve as a contemporary model for Indonesian Muslim society.